Investigation of the Appropriate Reverberation Time for Lower-Grade Elementary School Classrooms Using Speech Intelligibility Tests - A-Hyeon Jo; Chan-Jae Park; Chan-Hoon Haan (Buildings, 2022)
Because speech recognition performance is significantly lower at the age of nine or younger, the acoustic performance standards of classrooms for young children should be investigated. This study derives the appropriate reverberation time for lower-grade elementary school classrooms in Korea. A virtual sound field was created by computer modeling using normalized classrooms of Korean elementary schools. A total of five classrooms with reverberation times from 0.6 s to 1.2 s were produced by varying the sound absorption coefficient of the ceiling. Auralized sounds were produced by synthesizing anechoic sounds of words in a virtual sound field. Speech intelligibility tests were undertaken with 20 young students, aged nine. As a result, it was concluded that the reverberation time suitable for lower-grade classrooms of elementary schools should be below 0.6 s because test scores were significantly lower when RT was longer than this value.